2013
DOI: 10.1002/adma.201304803
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite‐Based Hybrid Solar Cells Exceeding 10% Efficiency with High Reproducibility Using a Thin Film Sandwich Approach

Abstract: Organometal halide perovskites have tremendous potential as light absorbers for photovoltaic applications. In this work we demonstrate hybrid solar cells based on the mixed perovskite CH3 NH3 PbI2 Cl in a thin film sandwich structure, with unprecedented reproducibility and generating efficiencies up to 10.8%. The successfulness of our approach is corroborated by the experimental electronic structure determination of this perovskite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
553
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 657 publications
(589 citation statements)
references
References 26 publications
34
553
0
2
Order By: Relevance
“…In contrast, the perovskite obtained from the reagent solution with PbCl 2 contains both I À and Cl À , giving the more complicated possibility of forming a mixed halide perovskite (CH 3 NH 3 PbI 3 À x Cl x ). Interestingly, in the mixed halide perovskite the exact location and the concentration of the Cl À remains unclear to date, with varying observations by several groups 1,20,[23][24][25][26] . The difficulty of detecting the Cl À in the mixed halide perovskite may partly be because of the detection limit of the techniques used; however, the fact that often only small quantities are observed suggests that the final content in the films may be very low.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the perovskite obtained from the reagent solution with PbCl 2 contains both I À and Cl À , giving the more complicated possibility of forming a mixed halide perovskite (CH 3 NH 3 PbI 3 À x Cl x ). Interestingly, in the mixed halide perovskite the exact location and the concentration of the Cl À remains unclear to date, with varying observations by several groups 1,20,[23][24][25][26] . The difficulty of detecting the Cl À in the mixed halide perovskite may partly be because of the detection limit of the techniques used; however, the fact that often only small quantities are observed suggests that the final content in the films may be very low.…”
Section: Resultsmentioning
confidence: 99%
“…However, the impact of the solution composition on perovskite crystal growth and film formation, and thus on the device performance, is still under scrutiny 20,21 . For example, it is challenging to form a smooth and continuous perovskite film on compact TiO 2 (c-TiO 2 )-coated fluorine-doped tin oxide (FTO) substrates by one-step solution coating of a solution containing lead iodide (PbI 2 ) or lead chloride (PbCl 2 ) blended with methylammonium iodide (CH 3 NH 3 I) 22,23 . A noncontinuous perovskite film is usually obtained, where pinholes can introduce shunting pathways limiting the solar cell performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned before, simple onestep methods often lead to inhomogeneous coverage of the substrates. [14,[102][103][104] In particular, Eperon et al studied the influence of the TiO 2 underlayer and its impact on perovskite-crystal formation when employing a non-stoichiometric mixture of MAI and PbCl 2 . They concluded that there is an www.advancedsciencenews.com unfavorable interaction between these layers, which leads to the growth of perovskite "pores", largely determined by the thickness of the perovskite film.…”
Section: One-step Depositionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Current record power conversion efficiency (PCE) of solar cells based on them has been boosted from initial value of 3.8%, 8 step by step, 16,17,5,[18][19][20][21] to current 22.1%. 22 During this process the breakthrough step is the first solid-state perovskite solar cell designed by Kim et al yielding the PCE exceeding 9%, 16 which triggered significant perovskite solar cell research activities and made PCEs dramatically enhanced within only shortly seven years.…”
Section: Introductionmentioning
confidence: 99%